Educação física escolar e cultura quilombola: um diagnóstico do ensino das práticas corporais na escola quilombola Santo André em Abaetetuba-PA e suas relações com a cultura quilombola - PINHEIRO, Jonas Gomes (2023)
This is a qualitative research that proposes as a theme School Physical Education and Quilombola Culture: A diagnosis of the Teaching of Corporal Practices at the Quilombola Santo André School in Abaetetuba-PA and its relations with the Quilombola Culture. With the transformations that occur in the contemporary world, it is necessary to think about the quality of teaching in schools, especially with regard to teaching aimed at schools that are in quilombola territory, in view of the difficult access to education and the appreciation of the culture of these communities. communities. In order to understand the paths that lead to the quality of this teaching, initially an extensive literature review was carried out from several authors who discuss and research on the theme of quilombola culture, body practices in the universe of School Physical Education and body practices in quilombola culture for a better understanding. In the second moment, the data collected from the interviews were analyzed, in order to facilitate understanding, the data were organized into four topics: 1) The practices of quilombola culture at the Quilombola Santo André School; 2) ARQUIA and Community: Participation and involvement with Quilombola Body Practices at School; 3) Quilombola Body Practices: Physical Education at School and the Political Pedagogical Project - PPP; 4) The Contribution of Physical Education to Quilombola Culture, which served for a better understanding of how Physical Education has been worked and thought at the Quilombola Santo André School in Abaetetuba-Pa. Altogether, four subjects were interviewed, these two Physical Education teachers, a director and the president of the Association of Remaining Communities of Quilombo das Ilhas de Abaetetuba, who work or maintain a relationship with the discipline of Physical Education and Quilombola Culture in the School. In this way, the present work seeks to present, in a general way, how the practices of the quilombola culture are or are not perceived in the Physical Education classes and in the daily life of the Quilombola Santo André School of the quilombola community of Baixo Itacuruça, in addition to seeking to point out how the practices of quilombola culture are understood and experienced by individuals responsible for the educational process in the community. Thus, it is believed that this work presents important questions for reflections on the meaning of the corporal practices of the quilombola culture at the Quilombola Santo André School in the municipality of Abaetetuba.